The driving prospects of sustainable environment in Malaysia / Nik Isyraq Hasif Nik Zainal - Nik Zainal, Nik Isyraq Hasif (Faculty of Business and Management, 2018)
This paper investigates the relationship between Carbon Dioxide Emissions (CO2) and the other factors such as Financial Development (FD), Energy Consumption (ENG), Economic Expansion (GDP) and Trade Openness (TO) in Malaysia. Annual time series data for the 1975 to 2014 period, the Autoregressive Distributed Lag (ARDL) and Unit Root Test such as Augmented Dickey Fuller (ADF) and Phillips Perron (PP) are used for the analysis. The results reveal that among the factors of GDP and TO have positive significant impact on GDP growth. However, FD and ENG are the only variables that does not have significant bearings to CO2 emissions in Malaysia. The study ultimately analyse the short run and long run elasticities of the model of sustainable development.